Exploring potential areas of future vaccine development for novel porcine circovirus type 3 (PCV3) - Janes, Erin (Kansas State University, 2020)
Porcine circoviruses have been circulating in swine herds for nearly 50 years, and from an evolutionary perspective, they may have existed before this. Most notably, pathogenic porcine circovirus type 2 (PCV2) has been a major economic concern to the swine industry. Porcine circovirus associated diseases have been linked to systemic, respiratory, enteric, and reproductive diseases, in addition to increased mortality rate in pigs. Successful vaccination programs with PCV2 vaccines have helped to control its spread and have led to a decrease in mortality rates in swine herds. Recently, porcine circovirus type 3 (PCV3), a novel porcine circovirus, has been identified and discovered to be circulating in numerous countries throughout the world. There is still more to understand about the pathogenesis and clinical presentation of PCV3, but numerous retrospective studies and some experimental infection studies have identified porcine circovirus associated disease-like syndromes in PCV3 infected pigs. Therefore, it is important to understand the potential impact this novel circovirus could have on the swine industry, including prevention strategies. Currently, there are no licensed vaccines available to aid in the prevention of disease caused by PCV3. This report aims to discuss the current state of PCV3 and explore potential areas of future vaccine development.
Keywords: PCV3; Porcine circovirus type 3; Porcine circovirus